Genome-wide Identification, Characterization, and Expression Analysis of PHT1 Phosphate Transporters in Wheat - Teng, Wan; Zhao, Yan-Yan; Zhao, Xue-Qiang; He, Xue; Ma, Wen-Ying; Deng, Yan; Chen, Xin-Ping; Tong, Yi-Ping (Frontiers in Plant Science, 2017)
The PHT1 family of phosphate (Pi) transporters mediates phosphorus (P) uptake and re-mobilization in plants. A genome-wide sequence analysis of PHT1 genes in wheat (Triticum aestivum) was conducted, and their expression locations and responses to P availability were further investigated. We cloned 21 TaPHT1 genes from the homologous alleles at TaPHT1.1 to 1.10 through screening a BAC library and amplifying genomic sequences. The TaPHT1 transporters were clustered into five branches in the phylogenetic tree of PHT1 proteins, and the TaPHT1 genes from a given branch shared high similarities in sequences, expression locations, and responses to P availability. The seven tested PHT1 genes all showed Pi-transport activity in yeast (Saccharomyces cerevisiae) cells grown under both low Pi and high Pi conditions. The expression of TaPHT1.1/1.9, 1.2, and 1.10 were root specific. The expression of these TaPHT1 genes at flowering positively correlated with P uptake after stem elongation across three P application rates and two wheat varieties in a field experiment. Therefore, modification of PHT1 expression may improve P use efficiency in a broad regime of P availability.